Tussen corporatisme en kapitalisme? : Stedelijke nijverheid en arbeid in achttiende-eeuws Vlaanderen - Ryckbosch, Wouter; Winter, Anne (TSEG - The Low Countries Journal of Social and Economic History, 2023)
This article uses returns by nineteen Flemish cities to an industrial survey undertaken by the central authorities in the Austrian Netherlands in 1738, to explore the state of urban industries in the County of Flanders on the eve of an economic revival that would lead into the first industrial revolution on the European continent. By focussing on three empirical questions – the extent and nature of industrial activity, the importance of craft guild organization, and indications of capitalist labour relations – the study aims to contribute to wider debates on the relationship between guilds and economic change in the run-up to industrialization. While the sundry nature of the data complicates their quantitative analysis, they provide valuable insight into the underlying diversity of both social realities and conceptions of ‘industry’ and ‘work’ in this period of transformation. The resulting image confirms a continued dominance of textile production in Flemish cities, in which mixed fabrics have replaced traditional woollens, while showing the tentative emergence of new consumption-culture oriented sectors (such as earthenware, tobacco, soap) and signalling the presence of varied organizational forms (workshops, manufactures, subcontracting, domestic workers, family labour). While the bulk of urban industrial activity was still craft-organized, this did not preclude the presence of highly proletarianized labour relations in both guild-based and non-guild-based activities.